Do first mover advantages for producers of energy efficient appliances exist? The case of refrigerators - Thomas Cleff; Klaus Rennings (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Energy efficiency regulation is an important driver for innovations in environmental technologies. Improvements of energy efficiency do not only contribute to reach envi-ronmental policy targets, they can be furthermore economically profitable. E.g. private households can reduce their costs in the long term by using efficient household appli-ances. But how can the specific competitive position on this market be assessed for German producers, and how strong is the competitiveness from firms coming from emerging economies? We analyse - as an example - the global refrigerator market, using the lead market approach for environmental innovations. As our results show, Germany has the most lead market potentials for energy-efficient refrigerators, followed by Korea und Italy. First mover advantages for high-tech energy efficient appliances can be realised on the German market. This is backed by high en-ergy efficiency standards in Europe which diffuse after some years to other countries. Since the pay-off time for energy efficient household appliances is with 7 to 10 years quite long, also a cost strategy with low prices can be successful. Especially in the case when the price of electricity and the national income are low. Markets for such products are for example in Asia and Russia. Producers use the existence of both strategy options to operate with different brands and product lines in different market niches at the same time. For firms in countries that do not have sufficient lead market potentials, innovations in energy efficiency must be targeted to fit the preferences of users in the lead market. The screening of the lead market can take on varying degrees of intensity. A good way for a company to estab-lish ties with a lead market is via producers with long experience on the Lead Market. It can be realised through a simple sales cooperation with local producers or a merger with a local producer of the lead market.
Keywords: Q55; O33; Q01; Q58; 330; Household appliances; energy efficiency; refrigerators; lead market; first mover